The New Encyclopedia of Southern Culture : Volume 5: Language - Abadie, Ann J.; Thomas, James G., Jr; Wilson, Charles Reagan; Johnson, Ellen, 1959-; Montgomery, Michael, 1950-2019 (Book collections on Project MUSE., 2007)
New Encyclopedia of Southern Culture: Volume 5: Language.